Copper-iron bimetallic Fenton-like catalyst as well as preparation method and application thereof

By preparing copper-iron bimetallic Fenton catalysts, the problems of low catalytic efficiency of iron-based catalysts and difficulty in recycling copper-based catalysts are solved, and the effect of efficient degradation of textile dyes and easy recovery is achieved.

CN119500134APending Publication Date: 2025-02-25CHANGZHOU TEXTILE GARMENT INST
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411880891.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The catalytic efficiency of existing iron-based catalysts is not high and the recycling of copper-based catalysts is difficult, which limits its application in textile dye degradation.

Method used

Using a copper-iron bimetallic Fenton catalyst, a catalyst with high catalytic activity and easy recovery is prepared by mixing copper salt, iron salt and γ-Al2O3 in deionized water, mechanical stirring, spray drying and calcining.

Benefits of technology

It realizes efficient degradation of textile dyes, and the catalyst is characterized by easy recycling and high catalytic efficiency, which reduces the preparation cost and improves the catalytic activity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119500134A_ABST
    Figure CN119500134A_ABST
Patent Text Reader

Abstract

The invention relates to a copper-iron bimetallic Fenton-like catalyst and a preparation method and application thereof.The preparation method comprises the steps that copper salt, iron salt and gamma-Al2O3 are mixed in deionized water and stirred through a mechanical stirring rod, and a mixed steeping liquor is obtained; carrying out spray drying on the mixed impregnation liquid on a spray dryer, and preliminarily removing moisture to obtain a precursor of the copper-iron bimetallic Fenton-like catalyst; and calcining the precursor of the copper-iron bimetallic Fenton-like catalyst in a tubular furnace to obtain the copper-iron bimetallic Fenton-like catalyst. The catalyst provided by the invention has the characteristics of easy recovery, high catalytic activity and the like, and solves the problems of low catalytic efficiency of an iron-based catalyst and difficult recovery of a copper-based catalyst in the prior art.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of material catalysis, and specifically relates to a copper-iron bimetallic Fenton catalyst and a preparation method and application thereof. Background Art

[0002] The Fenton-like oxidation process is one of the most powerful advanced oxidation processes and is widely used to degrade organic pollutants in wastewater. Compared with the traditional Fenton oxidation process, the Fenton-like oxidation process has greater potential for the treatment of waste organic matter due to its advantages in catalyst separation and recovery. Although Fenton-like catalysts have shown high catalytic activity, some Fenton-like catalysts have disadvantages such as a narrow working pH range and cumbersome preparation methods, which limit their practical application. Among various transition metals, copper is one of the more abundant ones. In addition, in the oxidation system in the presence of H2O2, Cu 2+ / Cu + Redox cycles are thermodynamically favorable. Therefore, copper-based Fenton-like catalysts have great application potential. Although many studies have confirmed that copper-based materials show good reactivity in initiating Fenton-like oxidation reactions, their catalytic efficiency still has room for improvement. For solid catalysts, their surface properties have a great influence on the catalytic efficiency. Therefore, improving the surface properties of copper-based catalysts is an effective way to fully realize their potential. In terms of the selection of catalyst carriers, γ-Al2O3 is a porous material with high specific surface area, high activity and strong adsorption properties. In addition, γ-Al2O3 is a metastable phase of alumina, which is more conducive to the dispersion and crystallization of metals on its surface.

[0003] Fenton-like reactions involve the catalytic generation of non-radical / free radical species that oxidize organic pollutants into non-toxic products such as H2O, CO2, and inorganic salts. They have good advanced oxidation technology in the degradation of textile wastewater, such as polyvinyl alcohol (PVA), rhodamine-B, and reactive red X-3B. PVA is a common textile slurry, and rhodamine-B and reactive red X-3B are commonly used in textile dyes. These two substances are often found in wastewater discharged from textile factories. In the traditional Fenton reaction, metal ions such as Fe 2+ It has high catalytic activity in homogeneous Fenton reactions, but it also has some disadvantages. For example, it is difficult to recover soluble metal ions from treated water. In addition, the catalytic activity of metal ions is highly dependent on pH (pH < 5.0). At inappropriate pH, metal hydroxide sludge will be formed. Therefore, Fenton-like catalysts that are easy to recycle and adapt to a wider pH range are attracting more and more attention from researchers. Among various transition metal oxides, Fe3O4 is an efficient heterogeneous catalyst that can be used to degrade organic pollutants. Due to Fe 2+The presence of can activate H2O2 to generate hydroxyl radicals, triggering a Fenton-like reaction. Fe3O4 has an inverse spinel structure, and electrons effectively transfer to Fe at the octahedral position. 2+ and Fe 3+ In addition, magnetite (Fe3O4) can be magnetically separated and recovered from wastewater. However, due to the neutral pH (optimum pH = 2.0-4.0) of Fe 3+ / Fe 2+ Due to the low redox cycle efficiency, the activity of commercial Fe3O4 as a Fenton-like catalyst is generally low [15,16]. In order to improve the catalytic activity of Fe3O4 at neutral pH, the introduction of another metal becomes a feasible strategy. In recent years, copper-containing solid catalysts have attracted much attention because their reaction mechanism is similar to that of iron-based catalysts, but they have better catalytic activity and acid and alkali resistance. Summary of the invention

[0004] The purpose of the present invention is to overcome the above-mentioned defects in the prior art and provide a copper-iron bimetallic Fenton catalyst and its preparation method and application. The catalyst has the characteristics of easy recovery and high catalytic activity, and at the same time solves the current problems of low catalytic efficiency of iron-based catalysts and difficulty in recovering copper-based catalysts.

[0005] A copper-iron bimetallic Fenton catalyst uses transition metal elements copper and iron as active centers, uses γ-Al2O3 as a catalyst carrier, and is mixed with copper salt, iron salt and γ-Al2O3.

[0006] A method for preparing a copper-iron bimetallic Fenton catalyst comprises the following steps: mixing a copper salt, an iron salt and γ-Al2O3 in deionized water, stirring the mixture using a mechanical stirring rod, and obtaining a mixed impregnation liquid; spray drying the mixed impregnation liquid on a spray dryer to preliminarily remove water, and obtaining a precursor of the copper-iron bimetallic Fenton catalyst; and calcining the precursor of the copper-iron bimetallic Fenton catalyst in a tubular furnace, and obtaining the copper-iron bimetallic Fenton catalyst.

[0007] The invention discloses an application of a copper-iron bimetallic Fenton catalyst for degrading textile dyes.

[0008] Compared with the prior art, the present invention has at least the following technical effects:

[0009] The copper-iron bimetallic Fenton catalyst provided by the present invention does not contain toxic metal elements, has little harm to the human body and the environment, and relative to precious metals and rare metal elements, copper and iron are relatively cheap, and the catalyst has low preparation cost. The catalyst uses copper and iron elements as active centers, γ-Al2O3 as a carrier, and is prepared by an impregnation-spray drying-calcination method. The catalyst has the characteristics of being easy to recover and having high catalytic efficiency. The catalytic performance of the copper-iron bimetallic Fenton catalyst is regulated by controlling the impregnation time, the process parameters of the spray dryer, and the calcination time of the tubular furnace. In addition, the raw materials for the production of the catalyst are simple and easy to obtain, the preparation process is simple, and efficient, stable, and economical production can be carried out, and the existing traditional Fenton reagent can be effectively replaced. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] Figure 1 This is an electron microscope image of the copper-iron bimetallic Fenton catalyst of the present invention;

[0011] Figure 2 The XRD diagram of the copper-iron bimetallic Fenton catalyst of the present invention before and after use;

[0012] Figure 3 It is a schematic diagram of the magnetic properties of the copper-iron bimetallic Fenton catalyst of the present invention;

[0013] Figure 4 It is a schematic diagram of the hysteresis loop of the copper-iron bimetallic Fenton catalyst of the present invention;

[0014] Figure 5 This is a comparison diagram of Rhodamine-B solution before and after degradation;

[0015] Figure 6 This is a comparison chart of Reactive Red X-3B solution before and after degradation. DETAILED DESCRIPTION

[0016] The embodiments of the present invention will be described in detail below in conjunction with examples. However, those skilled in the art will understand that the following examples are only used to illustrate the present invention and should not be construed as limiting the scope of the present invention. The specific conditions not specified in the examples are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used without indicating the manufacturer are all conventional products that can be purchased commercially.

[0017] A copper-iron bimetallic Fenton catalyst uses transition metal elements copper and iron as active centers, uses γ-Al2O3 as a catalyst carrier, and is mixed with copper salt, iron salt and γ-Al2O3.

[0018] Furthermore, in the present invention, based on the total mass of the catalyst on a dry basis, the molar ratio of γ-Al2O3, copper salt and iron salt is 0.6-1.5:4-8:6-12.

[0019] Furthermore, the particle size of the carrier γ-Al2O3 of the present invention is 20nm, and the specific surface area is 190-260m 2 / g.

[0020] Furthermore, the copper salt of the present invention is at least one of Cu(NO3)2·3H2O, CuCl2·3H2O, and Cu(SO4)2·5H2O;

[0021] Furthermore, the iron salt of the present invention is at least one of Fe2(SO4)3·7H2O, FeCl3·6H2O, and Fe(NO3)3·9H2O.

[0022] A method for preparing a copper-iron bimetallic Fenton catalyst comprises the following steps: mixing a copper salt, an iron salt and γ-Al2O3 in deionized water, stirring the mixture using a mechanical stirring rod, and obtaining a mixed impregnation liquid; spray drying the mixed impregnation liquid on a spray dryer to preliminarily remove water, and obtaining a precursor of the copper-iron bimetallic Fenton catalyst; and calcining the precursor of the copper-iron bimetallic Fenton catalyst in a tubular furnace, and obtaining the copper-iron bimetallic Fenton catalyst.

[0023] Furthermore, the preparation process of the present invention is impregnation-spray drying-calcination, the impregnation time is 3-10h, the mechanical agitator speed is 300-1000r / min, the feed amount is 100-2000mL / h, the inlet air temperature is 100-300°C, the nozzle diameter is 0.5-2mm, the calcination temperature is 350-550°C, and the heating rate is 2-8°C / h.

[0024] Furthermore, the reaction conditions of the copper-iron bimetallic Fenton catalyst of the present invention are as follows: the pH of the reaction solution is 3-9, the amount of catalyst is 1-5 g / L, the reaction temperature is 40-80°C, and the amount of H2O2 is 6-15 g / L.

[0025] The invention discloses an application of a copper-iron bimetallic Fenton catalyst for degrading textile dyes.

[0026] For iron-based solid catalysts, Fe 2+ The regeneration of (Equation (1)) is a necessary condition for the generation of ·OH (Equation (2)). In single-element catalysts, the generation rate of hydroxyl radicals is affected by Fe 3+ / Fe 2+ The redox rate is affected. Therefore, introducing additional metal elements becomes a reasonable choice. Adding copper can solve this problem. + Fe 3+The reduction of is thermodynamically favorable and promotes the regeneration of Fe. A synergistic reaction occurs between Fe and Cu (Equation (5)). In addition, Cu can also activate H2O2 to generate ·OH (Equations (3) and (4)), thus improving the catalytic activity of copper-iron bimetallic Fenton catalysts.

[0027] Fe 3+ +H2O2→Fe 2+ +HO2·+H + k=0.02 M -1 s -1 (1)

[0028] Fe 2+ +H2O2→Fe 3+ + OH+OH - k=76 M -1 s -1 (2)

[0029] Cu 2+ +H2O2→Cu + +HO2·+H + k = 4.6 × 10 2 M -1 s -1 (3)

[0030] Cu + +H2O2→Cu 2+ + OH+OH - k = 1.0 × 10 4 M -1 s -1 (4)

[0031] Fe 3+ +Cu + →Fe 2+ +Cu 2+ (5)

[0032] The present invention adopts an impregnation-spray drying-calcination method to prepare a copper-iron bimetallic Fenton catalyst with high dispersibility and easy recycling characteristics, which solves the current problems of low catalytic efficiency of iron-based catalysts and difficulty in recycling copper-based catalysts. The surface physical and chemical properties of the copper-iron bimetallic Fenton catalyst are characterized by testing techniques such as SEM and XRD, and the successful synthesis of the target bimetallic composite material is verified. The present invention uses PVA, rhodamine-B and reactive red X-3B, which are commonly used additives in the textile industry, as target pollutants, and evaluates the catalytic activity of the prepared copper-iron bimetallic Fenton catalyst in a Fenton-like system.

[0033] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0034] Example 1

[0035] This embodiment provides a copper-iron bimetallic Fenton catalyst, and the preparation method thereof comprises:

[0036] 1. Weigh γ-Al2O3, Cu(NO3)2·3H2O and Fe(NO3)3·9H2O at a molar ratio of 0.98-6.2-0.86, add into water to form 500mL mixed aqueous solution, and stir mechanically for 3h at a speed of 500r / min.

[0037] 2. Use a spray dryer to spray dry the mixed aqueous solution as raw material. Spray the mixed aqueous solution into the cavity. The dried copper-iron bimetallic Fenton catalyst precursor is collected by a connected cyclone separator. The feed rate is 500mL / h, the inlet air temperature is 180℃, and the nozzle diameter is 0.5mm.

[0038] 3. The copper-iron bimetallic Fenton catalyst was prepared by calcining the precursor of the copper-iron bimetallic Fenton catalyst in a tubular furnace under a nitrogen atmosphere. The calcination temperature was 400°C and the heating rate was 3°C / h.

[0039] Example 2

[0040] 1. Weigh γ-Al2O3, CuCl2·3H2O and Fe(NO3)3·9H2O at a molar ratio of 1.2-5.8-0.90, add into water to form 500mL mixed aqueous solution, and stir mechanically for 2h at a speed of 600r / min with a mechanical stirrer.

[0041] 2. Use a spray dryer to spray dry the mixed aqueous solution as raw material. Spray the mixed aqueous solution into the laboratory. The dried copper-iron bimetallic Fenton catalyst precursor is collected by a connected cyclone separator. The feed rate is 600 mL / h, the inlet air temperature is 190°C, and the nozzle diameter is 0.8 mm.

[0042] 3. The copper-iron bimetallic Fenton catalyst was prepared by calcining the precursor of the copper-iron bimetallic Fenton catalyst in a tubular furnace under a nitrogen atmosphere. The calcination temperature was 450°C and the heating rate was 4°C / h.

[0043] Example 3

[0044] 1. Weigh γ-Al2O3, CuCl2·3H2O and Fe(NO3)3·9H2O at a molar ratio of 1.2-5.8-0.90, add into water to form 500mL mixed aqueous solution, and stir mechanically for 2h at a speed of 600r / min with a mechanical stirrer.

[0045] 2. Use a spray dryer to spray dry the mixed aqueous solution as raw material. Spray the mixed aqueous solution into the laboratory. The dried copper-iron bimetallic Fenton catalyst precursor is collected by a connected cyclone separator. The feed rate is 600 mL / h, the inlet air temperature is 190°C, and the nozzle diameter is 0.8 mm.

[0046] 3. The copper-iron bimetallic Fenton catalyst was prepared by calcining the precursor of the copper-iron bimetallic Fenton catalyst in a tubular furnace under a nitrogen atmosphere. The calcination temperature was 450°C and the heating rate was 4°C / h.

[0047] Example 4

[0048] 1. Weigh γ-Al2O3, CuCl2·3H2O and Fe(NO3)3·9H2O at a molar ratio of 0.8-5.5-1.0, add into water to form 500mL mixed aqueous solution, and stir mechanically for 5h at a speed of 800r / min.

[0049] 2. Use a spray dryer to spray dry the mixed aqueous solution as raw material. Spray the mixed aqueous solution into the laboratory. The dried copper-iron bimetallic Fenton catalyst precursor is collected by a connected cyclone separator. The feed rate is 800 mL / h, the inlet air temperature is 170°C, and the nozzle diameter is 1.5 mm.

[0050] 3. The copper-iron bimetallic Fenton catalyst was prepared by calcining the precursor of the copper-iron bimetallic Fenton catalyst in a tubular furnace under a nitrogen atmosphere. The calcination temperature was 550°C and the heating rate was 5°C / h.

[0051] Example 5

[0052] 1. Weigh γ-Al2O3, CuCl2·3H2O and Fe(NO3)3·9H2O at a molar ratio of 1.0-5.2-0.9, add into water to form 500mL mixed aqueous solution, and stir mechanically for 5.5h at a speed of 65000r / min.

[0053] 2. Use a spray dryer to spray dry the mixed aqueous solution as raw material. Spray the mixed aqueous solution into the laboratory. The dried copper-iron bimetallic Fenton catalyst precursor is collected by a connected cyclone separator. The feed rate is 900 mL / h, the inlet air temperature is 200 ° C, and the nozzle diameter is 1.8 mm.

[0054] 3. The copper-iron bimetallic Fenton catalyst was prepared by calcining the precursor of the copper-iron bimetallic Fenton catalyst in a tubular furnace under a nitrogen atmosphere. The calcination temperature was 450°C and the heating rate was 6°C / h.

[0055] In order to further illustrate the performance of the catalyst provided by the present invention, the following experiments were conducted:

[0056] 1. PVA degradation test

[0057] Take a PVA solution with a concentration of 1-5g / L, and carry out the reaction under the conditions of pH 3-9, catalyst dosage of 1-5g / L, reaction temperature of 40-80℃, and H2O2 dosage of 6-15g / L. The physical and chemical properties of copper-iron bimetallic Fenton catalysts are characterized as follows Figure 1 , 2 and 4. From Figure 2 It can be seen that after the catalytic reaction, the copper-iron bimetallic Fenton catalyst can still maintain its original crystal phase structure, proving that the catalyst has good reaction stability. Figure 3 and Figure 4 It can be seen that the copper-iron bimetallic Fenton catalyst can be easily attracted by an external magnet in the solution after the reaction, so that the catalyst and the reaction solution can be effectively separated. The degradation test proves that the degradation rate of PVA by the copper-iron bimetallic Fenton catalyst can reach more than 96%.

[0058] 2. Rhodamine-B and Reactive Red X-3B degradation test

[0059] Take a solution of Rhodamine-B and Reactive Red X-3B with a concentration of 1-5g / L, and carry out the reaction under the conditions of pH 3-9, catalyst dosage of 1-5g / L, reaction temperature of 40-80°C, and H2O2 dosage of 6-15g / L. Figure 5 and Figure 6 It can be seen that the copper-iron bimetallic Fenton catalyst has a good degradation effect on Rhodamine-B and Reactive Red X-3B.

Claims

1. A copper-iron bimetallic Fenton catalyst, characterized in that The transition metal elements copper and iron are used as active centers, γ-Al2O3 is used as a catalyst carrier, and is mixed with copper salt, iron salt and γ-Al2O3.

2. The copper-iron bimetallic Fenton catalyst according to claim 1, characterized in that Based on the total mass of the catalyst on a dry basis, the molar ratio of γ-Al2O3, copper salt and iron salt is 0.6-1.5:4-8:6-12.

3. The copper-iron bimetallic Fenton catalyst according to claim 1, characterized in that The particle size of the carrier γ-Al2O3 is 20nm and the specific surface area is 190-260m 2 / g.

4. The copper-iron bimetallic Fenton catalyst according to claim 1, characterized in that The copper salt is at least one of Cu(NO3)2·3H2O, CuCl2·3H2O, and Cu(SO4)2·5H2O.

5. The copper-iron bimetallic Fenton catalyst according to claim 1, characterized in that The iron salt is at least one of Fe2(SO4)3·7H2O, FeCl3·6H2O, and Fe(NO3)3·9H2O.

6. A method for preparing the copper-iron bimetallic Fenton catalyst according to any one of claims 1 to 5, characterized in that Copper salt, iron salt and γ-Al2O3 are mixed in deionized water, and stirred with a mechanical stirring rod to obtain a mixed impregnation liquid; the mixed impregnation liquid is spray-dried on a spray dryer to preliminarily remove moisture to obtain a precursor of a copper-iron bimetallic Fenton catalyst; the precursor of the copper-iron bimetallic Fenton catalyst is calcined in a tubular furnace to obtain a copper-iron bimetallic Fenton catalyst.

7. The preparation method according to claim 6, characterized in that The preparation process is impregnation-spray drying-calcination, the impregnation time is 3-10h, the mechanical agitator speed is 300-1000r / min, the feed amount is 100-2000mL / h, the inlet air temperature is 100-300℃, the nozzle diameter is 0.5-2mm, the calcination temperature is 350-550℃, and the heating rate is 2-8℃ / h.

8. The preparation method according to claim 6, characterized in that The reaction conditions of the copper-iron bimetallic Fenton catalyst are as follows: the pH of the reaction solution is 3-9, the amount of catalyst is 1-5 g / L, the reaction temperature is 40-80°C, and the amount of H2O2 is 6-15 g / L.

9. An application of a copper-iron bimetallic Fenton catalyst, characterized in that Used to degrade textile dyes.

Citation Information

Cited By

  • Iron-based gel particle catalyst as well as preparation method and application thereof

    CN121490825A